2013
DOI: 10.1590/s0104-530x2013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Métodos de avaliação da implantação da manufatura enxuta: uma revisão da literatura e classificação

Abstract: Apesar da ampla literatura existente sobre Manufatura Enxuta (ME), pouco esforço tem sido dedicado a sintetizar o estado da arte sobre métodos que avaliam sua implantação. Nesse sentido, este artigo tem como objetivo apresentar uma revisão da literatura sobre métodos científicos de avaliação da implantação da ME, buscando identificar suas principais características. Foram identificados 48 artigos relacionados ao tema, no período de 1996 a agosto de 2012. Depois da revisão, as publicações foram classificadas, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 74 publications
2
8
0
1
Order By: Relevance
“…Regarding the literature review, the operationalization of the research through a case study corroborates the results found in Walter & Tubino (2013) in which they indicated the case study as the methodological approach most used in this area.…”
Section: Figure 2 -Results Of Evaluation Of Adoption Of Lean Manufactsupporting
confidence: 76%
See 1 more Smart Citation
“…Regarding the literature review, the operationalization of the research through a case study corroborates the results found in Walter & Tubino (2013) in which they indicated the case study as the methodological approach most used in this area.…”
Section: Figure 2 -Results Of Evaluation Of Adoption Of Lean Manufactsupporting
confidence: 76%
“…The survey considered six impact areas related to lean manufacturing principles and practices pointed out in the literature. Walter & Tubino (2013) carried out a review of the literature on the scientific methods related to the subject between 1996 and 2012. The authors point out the case study as the methodological approach most used in the area.…”
Section: Methods For Evaluation Of Lean Manufacturingmentioning
confidence: 99%
“…This study presents a better way to understand Lean strategies and techniques and the way they could be used in the companies. An evaluation mechanism could be implemented top show the evolution of the improvements presented in the companies (Walter & Tubino, 2013).…”
Section: Lean Manufacturing In Small and Medium Enterprises (Smes)mentioning
confidence: 99%
“…This method is widely used for the construction and refinement of operations management theory (Voss et al, 2002) and LPI. (Walter & Tubino, 2013). In addition, empirical studies allow a large number of variables to be investigated to identify new relationships among them (Wacker, 1998), as in the objective of this study.…”
Section: Overviewmentioning
confidence: 99%